PENGARUH LITERASI ANGGARAN DAN MEDIA SOSIAL TERHADAP PERSEPSI MAHASISWA TENTANG TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH - Arif Nadzirul Haq E; Bella Putrie Nindyawan (Jurnal Akuntansi Kompetif, 2026)
Transparency in regional financial management is an important foundation in creating accountable and trustworthy governance. This study explores how budget literacy and social media usage influence students' perceptions of transparency in regional financial management. The study used a quantitative approach with a survey method of 42 active accounting students who have taken public finance courses and have active social media accounts. Data were collected through a questionnaire compiled with a 5-point Likert Scale, then analysed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis using the SPSS application. The results showed that budget literacy significantly influenced students' perceptions of transparency in regional financial management, social media also significantly influenced students' perceptions of transparency in regional financial management, and both variables simultaneously significantly influenced students' perceptions of transparency in financial management. These findings indicate that increasing budget literacy and utilizing social media as a means of budget education can strengthen students' positive perceptions of transparency in regional financial management, thus implicating the need for more comprehensive financial literacy programs in higher education institutions.